Health benefits of wolfberry (Gou Qi Zi, Fructus barbarum L.) on the basis of ancient Chineseherbalism and Western modern medicine - Sun Wenli; Mohamad Hesam Shahrajabian; Cheng Qi (Mashhad University of Medical Sciences, 2021)
Objective: Goji berry has been used for thousand years inTraditional Chinese Medicine (TCM) in China and other Asian countries as foods to promote health and as drugs to treat diseases. It has been claimed this important medicinal crop is the good source of compounds with valuable nutritional and bioactive properties which can also provide industrial sustainability in organic life. Materials and Methods: All relevant papers in English language were collected. The keywords of wolfberry, goji berry, Chinese herbalism and western Medicine were searched in Google Scholar, Scopus, Research Gate and PubMed. Results: Besides its uses in food and culinary, wolfberry has long played important roles in TCM where they are believed to enhance immune system function, improve eyesight, protect liver, boost sperm production and improve circulation, among other effects. TCM calls for wolfberry to be prepared as a decoction or ground into a powder and mixed with other herbs. Additionally, Gojiberry is rich in ascorbic acid, thiamine and riboflavin. Moreover, Gojiberrycontains carbohydrates, organic acids, and so many minerals like potassium, sodium, phosphorus, magnesium, iron, calcium, zinc and selenium. Conclusion: This review article allowed verifying that wolfberry as asource of compounds with valuable nutritional and bioactive properties.